ANALISIS RISIKO KESEHATAN LINGKUNGAN (ARKL) PARAMETER AIR MINUM UNTUK PEKERJA DI KABUPATEN PASURUAN TAHUN 2017 - Linda Agustina (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2019)
Water is a basic necessity for life that most importance substance. Water must be available sufficiently in quality, quantity and continuity for human survival. Ideal drinking water should be clean, colorless, non-sticky and odorless. Drinking water should not contain pathogenic germs and all living things that endanger human health, do not contain chemicals that can change bodily functions and can be economically harmful. The purpose of this study is to analyze environmental health risks in drinking water parameters for workers in Pasuruan Regency in 2017. The method of this research is by collecting secondary data, which is 32 points of location of drinking water in Pasuruan Regency. Secondary data were obtained from the results of laboratory tests, and data on the various parameters of BBTKLPP laboratory examination along with SNI and related regulations and literature from several sources to support the available data. Then the secondary data obtained is calculated the maximum and minimum of concentration values, intake and health risk characteristics of each chemical agent in the parameters of drinking water. The research results show that the concentration of Fe in drinking water exceeds the predetermined quality standard, namely Cmax 0.8364.